2014
DOI: 10.1007/s00270-014-0967-1
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting Beads Loaded With Doxorubicin (DEBDOX) Chemoembolisation Before Liver Transplantation for Hepatocellular Carcinoma: An Imaging/Histologic Correlation Study

Abstract: Our data confirm the potential benefit of DEBDOX chemoembolisation as bridge therapy before LT, and they provide a rational basis for new studies focusing on recurrence-free survival after LT. Radiologic evaluation according to mRECIST criteria enables accurate prediction of tumour necrosis, whereas RECIST criteria do not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…In patients with HCC within the Milan criteria, bridging therapy is estimated to reduce the dropout rate to 0-10% [56]. Bland, chemotherapeutic, and radiotherapeutic embolization techniques have all shown to be similar bridging therapies in terms of safety and efficacy [57][58][59]. A recently conducted prospective study comparing 90 Y to cTACE in patients with either BCLC stage A or B found longer times to progression: >26 months in the 90 Y group versus 6.8 months in the cTACE group, p = 0.012, (HR 0.122, 95% CI, 0.027-0.557, p = 0.007), but similar tumor necrosis and median survival times.…”
Section: Bridge To Transplantmentioning
confidence: 99%
“…In patients with HCC within the Milan criteria, bridging therapy is estimated to reduce the dropout rate to 0-10% [56]. Bland, chemotherapeutic, and radiotherapeutic embolization techniques have all shown to be similar bridging therapies in terms of safety and efficacy [57][58][59]. A recently conducted prospective study comparing 90 Y to cTACE in patients with either BCLC stage A or B found longer times to progression: >26 months in the 90 Y group versus 6.8 months in the cTACE group, p = 0.012, (HR 0.122, 95% CI, 0.027-0.557, p = 0.007), but similar tumor necrosis and median survival times.…”
Section: Bridge To Transplantmentioning
confidence: 99%
“…43,44 All embolotherapies have shown similar safety and efficacy profiles for patients requiring bridging therapy. [45][46][47] Although there was no difference in OS, a prospective study of patients with either BCLC Stage A or B comparing SIRT to cTACE observed longer times to progression (TTPs) in the SIRT group in comparison to the cTACE group: >26 months in the SIRT group versus 6.8 months in the cTACE group, p ¼ 0.012 (hazard ratio [HR]: 0.122, 95% confidence interval [CI]: 0.027-0.557, p ¼ 0.007). The authors concluded that the longer TTP provided by radioembolization could potentially reduce dropout from transplant waitlists.…”
Section: Bridge To Transplantmentioning
confidence: 99%
“…It is generally believed that pre‐TACE treatment could also improve the prognosis after LT . Though many medical centers have studied on this, there is still no definite conclusion . In addition, no meta‐analyses have investigated on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] It is generally believed that pre-TACE treatment could also improve the prognosis after LT. [12][13][14] Though many medical centers have studied on this, there is still no definite conclusion. 15,16 In addition, no meta-analyses have investigated on this issue. Therefore, we conducted the meta-analysis of all available studies to systematically evaluate the effect of preoperative TACE on LT.…”
Section: Introductionmentioning
confidence: 99%